Alternative technique for the treatment of osteonecrosis in breasts: description and results - Leonardo David Pires Barcelos; Ognev Meireles Cozac; Marcela Caetano Cammarota; Leonardo Martins Costa Daher; Milena Carvalho Almeida Galdino; Ismar Ribeiro (Revista Brasileira de Cirurgia Plástica)
Introduction: This work describes and presents the results of an alternative technique for treating steatonecrosis by liposuction using a specific cannula, with good physical and imaging results. Steatonecrosis is a complication that frequently occurs during mammary surgeries, especially during mammary reconstructions and in conservative surgery or TRAM. Steatonecrosis is characterized initially by hardening of the tissue that may develop into nodules of different sizes in any mammary region with oily cysts and fibrosis; consequently, steatonecrosis is a constant concern for patients, oncologists, breast cancer specialists, and plastic surgeons due to the possibility of tumor recurrence. Method: A retrospective review of the medical records of the patients undergoing procedures related to the breast, either reconstructive or aesthetic, was performed. Patients who developed steatonecrosis and were treated by liposuction, similar to the bone drilling technique performed by orthopedic surgeons for the treatment of bone necrosis, were included in the study. Results: Eight patients from the study period reviewed were selected. The mean age was 56 years. Most of the patients showed deformity in the affected breast, with oily cysts, reported in 5 patients (62.5%), being the most common deformity. Breast cancer history was reported for 75% of the patients. Conclusion: The individualization of the patient is the key to successful treatment of steatonecrosis and an essential tool to satisfy the expectations and desires of the patient after this complication. Each technique has its indications, advantages and limitations, which should be thoroughly discussed with the patient to obtain the best possible result.